Water-soluble cutting fluid for preventing white rust and corrosion of aluminum alloy and preparation method of water-soluble cutting fluid
By forming a dense protective film on the surface of the aluminum alloy by a specific ratio of water-soluble cutting fluid components, the problems of white rust and corrosion of the aluminum alloy are solved, the protection effect and lubricating performance are improved, and it is adapted to a variety of processing conditions, and is environmentally friendly and recyclable.
Patent Information
- Application Number
- CN202510521977.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-24
- Publication Date
- 2025-08-05
AI Technical Summary
Aluminum alloys are prone to white rust and corrosion in high humidity and high heat environments, and existing cutting fluids are difficult to effectively protect.
The water-soluble cutting fluid components with a specific ratio include mineral oil, composite ester lubricants, fatty acids, anti-hard water agents, copper corrosion inhibitors, composite phosphate corrosion inhibitors, organic carboxylic acid alcoholamine reactants, non-ionic surfactants and defoaming agents, and oxidation and corrosion are prevented by forming a dense protective film on the surface of the aluminum alloy.
Effectively prevent rust and corrosion of aluminum alloys, improve lubricating performance, adapt to the processing needs of different models of aluminum alloys, meet various working conditions, and the formula is environmentally friendly and recyclable.
Smart Images

Figure CN120424702A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metalworking fluids, and in particular to a water-soluble cutting fluid for preventing white rust and corrosion of aluminum alloys and a preparation method thereof. Background Art
[0002] Aluminum alloy corrosion primarily manifests itself in two forms: surface discoloration and pitting. Surface discoloration, where the aluminum material gradually changes from its original silver color to black, does not cause pitting. Pitting, on the other hand, manifests as small, deep, localized areas of corrosion that sometimes connect to form larger cavities, within which white, powdery material precipitates.
[0003] White rust refers to a white oxide precipitate that forms on aluminum alloy surfaces in high humidity and heat environments. It's primarily caused by an oxidation reaction. Aluminum alloys oxidize in humid, salty air, producing aluminum oxide. Aluminum oxide is a white, powdery substance known as white rust. White rust is particularly prevalent during the rainy season. Common aluminum alloy corrosion and white rust conditions place high demands on the long-term protection provided by cutting fluids. Summary of the Invention
[0004] In order to solve the above technical problems, the present invention provides a water-soluble cutting fluid capable of protecting aluminum alloy from white rust and corrosion and a preparation method thereof.
[0005] The technical solution is as follows: A water-soluble cutting fluid for preventing white rust and corrosion of aluminum alloys, the key point of which is to select raw materials that are non-corrosive to aluminum alloys, which includes the following components in parts by weight:
[0006] Mineral oil 30-50%;
[0007] Complex ester lubricant 5-15%;
[0008] Fatty acids 3-10%;
[0009] Anti-hard water agent 0.5-3%
[0010] Copper corrosion inhibitor 0.5-3%;
[0011] Composite phosphate corrosion inhibitor 1-3%;
[0012] Organic carboxylic acid alcohol amine reactant 5-15%;
[0013] Nonionic surfactant 2-5%;
[0014] Defoaming agent 0.1-0.3%;
[0015] Water balance.
[0016] Preferably, the mineral oil is 28# naphthenic mineral oil, which has better emulsification, lubricity and stability than general mineral oil.
[0017] Preferably, the ester lubricant is polyester and self-emulsifying synthetic ester in a ratio of 1:2, and the composite combination has better lubrication and emulsification effects.
[0018] Preferably, the fatty acid is tall oil, ricinoleic acid, oleic acid, or sulfonated fatty acid, which has the functions of assisting lubrication, emulsification, and adjusting pH value.
[0019] Preferably, the anti-hard water agent is fatty alcohol polyoxyethylene ether carboxylic acid, which enhances the stability of the cutting fluid diluent under hard water conditions.
[0020] Preferably, the copper corrosion inhibitor is benzotriazole and methylbenzotriazole derivatives in a ratio of 1:2, and they are combined to achieve better corrosion inhibition function for non-ferrous metals.
[0021] Preferably, the composite phosphate corrosion inhibitor is one or more of polyoxyethylene oleyl ether phosphate LB400, HORDAPHOS MDIT phosphate, and Rhodafac ASI80 phosphate.
[0022] Preferably, the organic carboxylic acid alcohol amine reactant is a reactant formed by one or more of undecane dibasic acid, dodecanedioic acid, and tribasic acid and one or more of methyldiethanolamine, diglycolamine, triethanolamine, and special alcohol amine CHO20J. In this system, the surface of the aluminum alloy is assisted in forming a film, so that the effective protective substance is spread more evenly on the surface of the aluminum alloy, thereby forming a dense protective film to prevent moisture and impurities in the air from corroding the metal surface, thereby achieving a long-term anti-corrosion effect.
[0023] Preferably, the nonionic surfactant is one or more of fatty alcohol polyoxyethylene ether, Guerbet 16 alcohol, isomeric 14-15 mixed alcohol, and semi-branched isomeric 12-13 mixed alcohol, to adjust the surface tension and the stability of the stock solution.
[0024] Preferably, the defoaming agent is organosiloxane.
[0025] A method for preparing a water-soluble cutting fluid for preventing white rust and corrosion of aluminum alloys comprises the following steps:
[0026] S1: Add the mineral oil, complex ester lubricant, fatty acid, anti-hard water agent, copper corrosion inhibitor, and complex phosphate corrosion inhibitor into the reactor in sequence, control the temperature at 35-45°C, and stir the reaction for 5-10 minutes;
[0027] S2: Add the organic carboxylic acid alcohol amine reactant after the reaction is completed, the reaction temperature of the reactant is 70-80°C, and stir for 30 minutes;
[0028] S3: adding nonionic surfactant;
[0029] S4: adding a defoaming agent and the remaining amount of water in sequence, stirring thoroughly, and obtaining the water-soluble cutting fluid for preventing white rust and corrosion of aluminum alloy.
[0030] Compared with the existing technology, the present invention has the following beneficial effects: compared with traditional cutting fluids, the cutting fluid focuses on the research of wetting properties and aluminum alloy surface reaction film-forming technology, and the cutting fluid is adapted to the requirements of corrosion protection and white rust prevention of different types of aluminum alloys. The long-chain nonionic surfactant and fatty acid emulsifier have better wetting and permeability on the aluminum alloy surface, allowing the organic carboxylic acid alcohol amine reactant to better adsorb and form a film on the aluminum alloy surface, and the reaction groups on the composite copper corrosion inhibitor and phosphate molecules interact with the metal ions generated in the corrosion process to form a dense insoluble layer, which is further polymerized on the metal surface to form a protective layer for adsorbing metal ions, thereby preventing oxidation and corrosion processes, effectively isolating the metal from contact with the corrosive medium, and preventing corrosion of the aluminum alloy;
[0031] At the same time, it is combined with complex ester lubricants, fatty acids, etc. to greatly improve the lubrication performance of the cutting fluid, which has reached the level required for various processing methods of aluminum alloys. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic diagram of the process of the present invention;
[0033] Figure 2 This is a diagram of the diameter of the abrasion in Example 1;
[0034] Figure 3 This is a diagram of the diameter of the abrasion in Example 2;
[0035] Figure 4 This is a diagram of the diameter of the abrasion in Example 3;
[0036] Figure 5 This is a diagram of the diameter of the abrasion in Example 4;
[0037] Figure 6 This is a diagram of the diameter of the abrasion in Example 5;
[0038] Figure 7 This is the corrosion performance diagram of 7075 aluminum alloy in Example 1;
[0039] Figure 8 This is a corrosion performance diagram of the 2024 aluminum alloy in Example 1;
[0040] Figure 9 This is the corrosion performance diagram of 7075 aluminum alloy in Example 2;
[0041] Figure 10This is the corrosion performance diagram of the 2024 aluminum alloy in Example 2;
[0042] Figure 11 This is the corrosion performance diagram of 7075 aluminum alloy in Example 3;
[0043] Figure 12 This is the corrosion performance diagram of the 2024 aluminum alloy in Example 3;
[0044] Figure 13 This is the corrosion performance diagram of 7075 aluminum alloy in Example 4;
[0045] Figure 14 This is the corrosion performance diagram of the 2024 aluminum alloy in Example 4;
[0046] Figure 15 This is the corrosion performance diagram of 7075 aluminum alloy in Example 5;
[0047] Figure 16 This is the corrosion performance diagram of the 2024 aluminum alloy in Example 5. DETAILED DESCRIPTION
[0048] The present invention will be further described below with reference to the embodiments and accompanying drawings.
[0049] Example 1
[0050] A water-soluble cutting fluid for preventing white rust and corrosion of aluminum alloys, the components and proportions of which are shown in Table 1 below:
[0051] Table 1 Components of Example 1
[0052]
[0053]
[0054] A method for preparing a water-soluble cutting fluid for preventing white rust and corrosion of aluminum alloy comprises the following steps:
[0055] Step 1: Add the mineral oil, complex ester lubricant, fatty acid, anti-hard water agent, copper corrosion inhibitor, and complex phosphate corrosion inhibitor into the reactor in sequence, control the temperature at 35-45° C., and stir the reaction for 5-10 minutes;
[0056] Step 2: Add the organic carboxylic acid alcohol amine reactant after the reaction is completed, the reaction temperature of the reactant is 70-80°C, and stir for 30 minutes;
[0057] Step 3: Add nonionic surfactant;
[0058] Step 4: Add defoaming agent and the remaining amount of water in sequence, and stir thoroughly to obtain the water-soluble cutting fluid for preventing white rust and corrosion of aluminum alloy.
[0059] Examples 2-5
[0060] Compared with Example 1, the components and proportions of Examples 2-5 are different, but the preparation methods are the same. The components and proportions of Examples 2-5 are shown in Table 2 below:
[0061] Table 2 Components of Examples 2-5
[0062]
[0063]
[0064] Test example
[0065] The above examples 1-5 were tested according to three standards, which are:
[0066] Standard 1: GB-T 6144-2010 "Synthetic Cutting Fluids", used for testing appearance, storage stability, dilution appearance, pH value, defoaming properties, surface tension, and paint compatibility;
[0067] Standard 2: JB / T 7453-2013 "Semi-synthetic Cutting Fluid", used for diluent stability, salt tolerance, hard water adaptability, rust prevention test, and corrosion test;
[0068] The detection method uses self-built experimental methods including:
[0069] Self-built 1: Lubricity test method,
[0070] Self-built 2: Aluminum alloy white rust and corrosion performance test method
[0071] Self-built 3: interlayer corrosion.
[0072] Test Example 1
[0073] Self-built 1: Lubricity test method:
[0074] Xiamen Tianji's MS-10A four-ball friction tester tests the PB value and wear spot condition of the cutting fluid;
[0075] Loading range: 49~9800N
[0076] Spindle speed: 50~3000r / min
[0077] Wear spot measurement accuracy: 0.001mm
[0078] Test steel ball: 12.7mm
[0079] The TTTsystem G8 lubricant tester from Microtap of Germany tests the tapping torque value of cutting fluids and compares the lubrication performance of cutting fluids.
[0080] Test material: 7075MAF, size 3.7mm*20mm
[0081] Tap tool: TTT T-M4F-TINT 3.644mm
[0082] Setting parameters: Speed: 1200rpm, Depth: 12mm, Maximum torque: 400Ncm
[0083] Test Example 2
[0084] Self-built 2: Aluminum alloy corrosion performance test method: immerse 7075 and 2024 in a beaker for 15 days and observe the growth of white rust and corrosion;
[0085] Test Example 3
[0086] Self-built 3: electrochemical corrosion:
[0087] a) Sample preparation:
[0088] 1) Prepare materials: bolts (alloy steel), cadmium-plated washers (cadmium-plated steel), nuts (cadmium-plated steel), bolts (titanium alloy, aluminum-plated), washers (alloy steel, cadmium-plated), nuts (alloy steel, cadmium-plated) medium and thick plates - any applicable specifications, such as 150mmx150mmx150mm, each of the following materials: 7075-T6 bare aluminum in accordance with AMS QQ-A-250 / 12
[0089] Cadmium-titanium-plated 4340M steel (1900-2000 MPa) conforming to AMS6417 or BMS7-26, Type I; Ti-6AL-4V titanium alloy conforming to AMS4911. Note: There are no strict restrictions on the size and thickness of individual plates, except for thicknesses less than 6 mm and for total lamination thickness exceeding 110 mm. Multiple washers can be used to compensate for the available bolt length.
[0090] 2) Preparation of medium and thick plates for testing: Cut the medium and thick plates to the appropriate size and machine the surface roughness to Ra32 with an unevenness within 0.005 mm (approximately). Using an approved diluted cutting fluid, first drill holes sequentially on the medium and thick plate stacks such as aluminum, steel, and titanium.
[0091] 3) Heat treatment of strengthened steel specimens to achieve a strength of 1900 MPa to 2000 MPa;
[0092] 4) Using added chromate conversion, cadmium-titanium plating.
[0093] b) Test steps:
[0094] 1) Using the test fluid (the concentration required for identification, if it is a water-soluble fluid, dilute it with tap water or industrial water), drill and ream the laminated specimen using a titanium nitride-coated reamer in two steps. The steps are as follows:
[0095] Step 1-Diameter 12300mm+0005 / -0000mm
[0096] Step 2 - Diameter 12700mm + 0005 / -0000mm
[0097] 2) Record drilling type, machine acceleration and tool feed;
[0098] 3) Insert the three fasteners in 2.2.2.4a) and tighten them so that the two middle plates are in contact with each other;
[0099] 4) Within 72 hours after the laminate test piece is assembled, expose the assembly to 60°C + 2°C and 50% + 5% relative humidity for 28 days;
[0100] 5) At the end of the test period, remove the laminated test piece from the box or furnace, allow it to cool and disassemble it;
[0101] 6) Check the external surface of the hole for corrosion.
[0102] C) Evaluation of test results: There was no evidence of pitting corrosion in any of the alloys.
[0103] The test results of Examples 1-5 are shown in Table 3 below:
[0104] Table 3 Test results
[0105]
[0106]
[0107]
[0108] Detection conclusion: From the experimental results in Table 3, it can be obtained that the wettability, from the surface tension, the smaller the surface tension, the smaller the contraction force, so the easier it is to spread on the surface and the stronger the permeability. From the data, the surface tension value of Example 1 is the smallest; from the average value of tapping torque, it can be seen that the torque values of Examples 1 and 2 are the smallest. Under the same PB value pressure, the wear spot diameter is the smallest, and the corresponding lubrication performance is better. Rust resistance, the rust resistance of single and laminated sheets are qualified. As for the corrosion resistance of aluminum, the test results of Examples 1-5 in Standard 1, Self-built 2, and 3 are all qualified. Comprehensively considering wettability, lubrication, aluminum alloy white rust, and corrosion, Example 1 is the best.
[0109] Finally, it should be noted that the above description is only a preferred embodiment of the present invention. Under the guidance of the present invention, ordinary technicians in this field can make various similar expressions without violating the purpose and claims of the present invention. Such changes fall within the scope of protection of the present invention.
Claims
1. A water-soluble cutting fluid for preventing white rust and corrosion of aluminum alloys, characterized by: The raw materials that are non-corrosive to aluminum alloy are selected, and the raw materials include the following components in parts by weight: Mineral oil 30-50%; Complex ester lubricant 5-15%; Fatty acids 3-10%; Anti-hard water agent 0.5-3% Copper corrosion inhibitor 0.5-3%; Composite phosphate corrosion inhibitor 1-3%; Organic carboxylic acid alcohol amine reactant 5-15%; Nonionic surfactant 2-5%; Defoaming agent 0.1-0.3%; Water balance.
2. The water-soluble cutting fluid for preventing white rust and corrosion of aluminum alloy according to claim 1, characterized in that: The mineral oil is 28# naphthenic mineral oil; The ester lubricant is a mixture of polyester and self-emulsifying synthetic ester; The fatty acid is one or more of tall oil, ricinoleic acid, oleic acid, and sulfonated fatty acid. The anti-hard water agent is fatty alcohol polyoxyethylene ether carboxylic acid.
3. The water-soluble cutting fluid for preventing white rust and corrosion of aluminum alloy according to claim 2, characterized in that: The ester lubricant is mixed in a dosage ratio of polyester to self-emulsifying synthetic ester = 1:
2.
4. The water-soluble cutting fluid for preventing white rust and corrosion of aluminum alloy according to claim 1, characterized in that: The copper corrosion inhibitor is a mixture of benzotriazole and methylbenzotriazole derivatives.
5. The water-soluble cutting fluid for preventing white rust and corrosion of aluminum alloy according to claim 4, characterized in that: The mixing ratio of the copper corrosion inhibitor is benzotriazole and methylbenzotriazole derivative = 1:
2.
6. The water-soluble cutting fluid for preventing white rust and corrosion of aluminum alloy according to claim 1, characterized in that: The composite phosphate corrosion inhibitor is one or more of polyoxyethylene oleyl ether phosphate LB400, HORDAPHOS MDIT phosphate, and Rhodafac ASI80 phosphate; The organic carboxylic acid alcohol amine reactant is a reactant formed by reacting one or more of undecane dicarboxylic acid, dodecanedioic acid, and tricarboxylic acid with one or more of methyldiethanolamine, diglycolamine, triethanolamine, and special alcohol amine CHO20J; The nonionic surfactant is one or more of fatty alcohol polyoxyethylene ether, Guerbet 16 alcohol, isomeric 14-15 mixed alcohol, and semi-branched isomeric 12-13 mixed alcohol.
7. The water-soluble cutting fluid for preventing white rust and corrosion of aluminum alloy according to claim 1, characterized in that: The defoaming agent is organosiloxane.
8. A method for preparing a water-soluble cutting fluid for preventing white rust and corrosion of aluminum alloys, characterized in that: The following steps are involved: S1: adding the mineral oil, complex ester lubricant, fatty acid, anti-hard water agent, copper corrosion inhibitor, and complex phosphate corrosion inhibitor to a reactor in sequence, controlling the temperature, and fully stirring the reaction; S2: adding the organic carboxylic acid alcohol amine reactant after the reaction is completed; S3: adding nonionic surfactant; S4: adding a defoaming agent and the remaining amount of water in sequence, stirring thoroughly, and obtaining the water-soluble cutting fluid for preventing white rust and corrosion of aluminum alloy.
9. The method for preparing a water-soluble cutting fluid for preventing white rust and corrosion of aluminum alloy and a preparation method thereof according to claim 8, characterized in that: In the step S1, the temperature is controlled at 35-45° C., and the stirring reaction time is 5-10 min.
10. The method for preparing a water-soluble cutting fluid for preventing white rust and corrosion of aluminum alloy and a preparation method thereof according to claim 8, characterized in that: In the step S2, the reaction temperature is 70-80°C.